Peningkatan Kualitas SDM dalam Pengelolaan Media Sosial pada Sektor UMKM - Rustamaji, Army Cahya Putra; Nugroho, Arif Widodo; Sandi, Prasetyo Hari; Putra, Ilham Muhammad Mardi (Abdimas Indonesian Journal, 2024)
Community service with a focus on improving the quality of human resources in managing social media in the MSME sector is carried out with the aim of providing increased knowledge and experience to business actors, especially in the use of information technology. With the rapid growth of information technology, the MSME sector is also increasingly dependent on this technology to develop their business. Many MSME players are still not effective in utilizing information technology such as social networks and websites to develop their MSME business and still do not understand the use of technology and social media in branding strategies which are currently popular. With this community service program, a solution to this problem will be provided through providing training to improve HR capabilities in managing social media in the MSME sector. In its implementation, this community service activity is carried out directly for the Patah Hati Coffee business actors. With this event, it is hoped that knowledge regarding the use of social media will increase for business actors.